Anthropogenic relief changes in a long‐lasting lignite mining area ('Ville', Germany) derived from historic maps and digital elevation models. Issue 9 (13th March 2021) - Henselowsky, Felix; Rölkens, Julian; Kelterbaum, Daniel; Bubenzer, Olaf
Abstract: Humans constitute one of the main geomorphological agents in modern times. As an example, post‐mining regions represent a typical landscape of the Anthropocene. Strong relief modifications are particularly obvious with open pit mining. However, many existing mining areas are lacking detailed pre‐mining information for the quantification of anthropogenic relief changes, which is a considerable challenge in regions with historic mining activities. Here, the Ville (Rhenish lignite district, Germany) is used to quantify surface mining induced relief changes in one of the oldest and currently largest lignite districts in Europe. Historical maps from first geodetic mapping in 1893 enabled construction of a historic digital elevation model to quantify the relief changes in comparison to elevation data from 2000 and 2015. The vertical accuracy of the historic data is remarkably high, with relief differences < 2 m in areas not affected by mining. In total, 49.2% of the investigated area (184 km 2 ) shows a relief deficit and 14.5% has positive relief differences. Absolute changes account for more than 80 m heightening (dumpsites of overburden) and lowering of the natural relief (pits). Besides these altitudinal changes, overall steeper slopes are significant for the new topography, but levelling exists likewise. The spatial variabilities are discussed in the context of the regional geology and the mining techniques. Undoubtedly, such large‐scale anthropogenic relief changes persist for a very long time and will last as a human legacy far into the future. Only the detailed reconstruction of the pre‐mining relief offers the ability to clarify the dimension of humans as geomorphological agents and to understand landscape perception. Due to the fact that the impact of open pit mining has such a large vertical and horizontal extension, their consideration as part of anthropogeomorphology can significantly contribute to support future Critical Zone research in the Anthropocene. Abstract : Computation of a digital elevation model based on historic geodetic maps (Preußische Neuaufnahme, 1893) allows the quantification of relief differences from historic time to nowadays in one of the largest and oldest historic lignite mining areas worldwide ('Ville', Germany). This highlights humans as geomorphological agents and anthropogeomorphology to study landscapes of the Anthropocene.